Chest radiological features of pulmonary histiocytosis X: a report based on 50 adult cases. Issue 2 (February 1982) - Lacronique, J; Roth, C; Battesti, J P; Basset, F; Chretien, J
Abstract : This study describes the chest radiographs of 50 adult patients with histologically verified histiocytosis X, proposes a radiological classification, and examines the role of radiology in assessing the prognosis of the disease. Radiologically the lesions predominate in the middle and lower lung fields, usually sparing the costophrenic angles, and are typically micronodular, reticular, or cystic. These features are especially suggestive of histiocytosis X if lung volume is normal or increased, there is an associated pneumothorax, they occur in a young male and there are no other intrathoracic changes (pleural or mediastinal). The three evolutionary patterns of improvement, stabilisation, and worsening are analysed with respect to the initial radiological features; one which carries a good prognosis is sparing of both costophrenic angles.